Hubungan Indonesia-Malaysia: Perspektif Budaya dan Keserumpunan Melayu Nusantara - Zed, Mestika (TINGKAP, 2015)
This working paper aims to discuss the relationship between Indonesia and Malaysia in the perspective of culture, especially in the light of the spirit of a kinship-relation of Melayu Nusantara (the Malay Archipelago). Both cultural concept and cluster spirit are basic elements and form an eternal 'determinant', but its meaning and forms could change over the time. This might be so because many contemporary issues are also clouded by many factors, either internal or external. There are many cases could be dicussed in terms of recently called as a cultural diplomacy. The most crucial cases in recent, among others, are the problem of migrant workers, border issues and cultural claims between the two countries. However, when we examined furthermore, it seems that many cases that appear on the surface recently had been actually more complicated than that of we could understand so far. Â This working paper will address the following questions: 1) How could we understand the concept of culture and kinship-cluster between Indonesia and Malaysia in the context of the past and present? 2) Does cultural, religion and kinship-cluster similiarities which are shaped through a long historical process colud be helpful for explaining and solving recent problems? 3) How could we read contemporary critical issues in bilateral relations between the two countries by way of using the lens a cultural diplomacy on behalf the spirit of kinship-cluster of Malay Archipelago? And 4) Based on this persepctive, what are then the concrete steps that can be done in addressing critical issues in relations between the two countries today? Â It will aslo discuss some of the challenges involving future bilateral relations. A conclusion will close this paper.Keywords: Melayu Nusantara, cultural diplomacy, kinship-cluster and bilateral relation.